Analysis of factors affecting company value with EPS as a moderation variable - Heliani, Heliani; Herdina, Vina; Gumelar, Taofik Muhammad (Master in Accounting Program, Faculty of Business & Economics, Universitas Islam Indonesia, Yogyakarta, Indonesia, 2024)
This study was conducted to analyze the factors that affect company value with EPS as a moderation variable in real estate and property subsector companies listed on the IDX for the 2017-2021 period. In this study, factors that affect company value use Intellectual Capital, Collateralizable Assets, and Dividend Policy. This research used secondary data is the company's financial statements published in the 2017-2021 on the IDX and has 10 companies for the population. The methods used are descriptive analysis, classical assumption test, moderation regression analysis, and hypothesis test. The results of this study are intellectual capital and collateralizable assets, each of which affects the value of the company. While the dividend policy has no effect on the value of the company. EPS do not moderate the effect of collateralizable assets on company value. EPS successfully moderates the influence of intellectual capital on company value and dividend policy on company value.